(untitled) (Security Dialogues, 2025)
This paper aims to present the negative impacts of politics and corruption on sports as a social phenomenon, which, due to such malign influences, is increasingly moving away from its original humanistic concept. The impact of politics and corruption is driving sports towards dehumanisation and national, religious, and racial discrimination of all its participants. Sports have become a battleground for power struggles between superpowers and small states, with nationalism and xenophobia imposing characteristics that contradict the very essence of sports. Today, sports are a crucial aspect of the ideological operations of systems that use sports to solve certain problems or as a mobilising force to support the system. Often, sports are treated as a means of achieving the basic ideological goals of society or the government. Sports have become an ideological tool to deceive the masses and maintain the control of the ruling powers. The integration of politics, sports, and power allows sports to be turned into entertainment for the masses, and under the motto “bread and circuses,” the people are turned into an audience, a crowd, which, through repressive behaviour control, absorbs social discontent arising from the marginal social position of certain groups. Sports are suitable for influencing the masses, especially the youth, and for affirming various political ideologies and social anomalies and irregularities. Therefore, corruption, a negative phenomenon that has not spared sports despite its initially noble assumptions, is not new. In one form or another, it has always existed. Corruption appears in various forms throughout sports, undermining honesty, fair play, and trust in the game. The increasing amounts of money inherent in sports make this industry susceptible to corruption, while the participants become addicted to power, elitism, and betting.